Performance Test of gPhone (#123, #126, and #127) in Kyoto and ITB Jatinangor. (August 2016) - Wahyudi, E J; Fukuda, Y; Nishijima, J; Itakura, M
Abstract: Gravity team of ITB, Kyoto University, and Kyushu University plan to carry out super hybrid measurement to monitor Carbon Capture Storage (CCS) injection in Gundih. During preparation stage and baseline survey before injection phase, gravity team analyze gPhone performance. Performance test of gPhone gravimeters in 2014 conducted in Kyoto and Jatinangor (three gPhone (#123, #126, and #127) placed in the same location). The tidal analysis program BAYTAP-G was used to decompose the gravity data into four components (tidal, trend, irregular, and response for auxiliary data). Response component in Kyoto relatively has lower frequency compare to Jatinangor, due to differences of the two measurement location. Response component from the longest time recording data (gPhone #123) give similiar pattern as gPhone #126, while gPhone #127 slightly different. Average standard deviation of the response component of three gPhone (#123, #126, and #127) respectively were 0.8, 1.0, and 1.9 μGal. Best drift achieved from this test show possibility to reach -4 to 5 pGal/day. Although gPhone #126 records different trend, but from tidal analysis comparison shows similiarity with gPhone #123.